Cyber attacks and privacy protection distributed consensus algorithm for multi-agent systems - Ming XU; Baojun ZHANG; Yiming WU; Chenduo YING; Ning ZHENG (Tongxin xuebao)
To solve the consensus problem of multi-agent systems in the environment of cyber attacks and information eavesdropping, an average consensus algorithm that can effectively resist network denial of service (DoS) attacks and protect nodes’ state privacy was proposed.Firstly, combined with the characteristics of DoS attacks in networked control systems, a periodic DoS attack model related to time was constructed.Then a distributed network node information processing mechanism based on differential privacy was proposed by using the information interaction between neighbor nodes, and then it was introduced into the average consensus algorithm.Furthermore, combined with the event-triggered mechanism, a consensus algorithm method suitable for undirected communication networks under DoS attacks was proposed, and its convergence and privacy protection performance were analyzed strictly mathematically.Finally, the effectiveness of the proposed algorithm was verified by a numerical simulation experiment and hardware experiment.